2001
DOI: 10.1139/z01-106
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and systematics of the northern African wood mouse (Apodemus sylvaticus) populations: a comparative study of mtDNA restriction patterns

Abstract: Conflicting hypotheses have been fonnulated regarding the origin of wood mouse (Apodemus sylvaticus) populations in northern Africa. ln this study, the mtDNA restriction patterns of mice (n = 28) collected in Tunisia andMorocco are compared with those of representatives from southern Europe (n = 102). The neighbour-joining tree confinns the existence of the three lineages preyiously found in the Mediterranean area: western, Tyrrhenian-BaIkan, and Sicilian. The western group is isolated from the two others, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
(11 reference statements)
5
32
1
Order By: Relevance
“…Finally, CR1 mismatch distribution indicated that population expansion in northern Algeria predated that in Europe (data not shown), confirming that the northern Algerian population is older (Brandli et al 2005). Similar molecular studies involving translocations of micromammals identified the geographic sources of European populations in Morocco or Tunisia, but in every case samples from Algeria were missing (Libois et al 2001;Michaux et al 2003;Brandli et al 2005;Cosson et al 2005).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Finally, CR1 mismatch distribution indicated that population expansion in northern Algeria predated that in Europe (data not shown), confirming that the northern Algerian population is older (Brandli et al 2005). Similar molecular studies involving translocations of micromammals identified the geographic sources of European populations in Morocco or Tunisia, but in every case samples from Algeria were missing (Libois et al 2001;Michaux et al 2003;Brandli et al 2005;Cosson et al 2005).…”
Section: Discussionmentioning
confidence: 52%
“…As a consequence, we expect that at least some dating events proposed for the recently introduced populations across the Mediterranean Basin are likely overestimated. It is thus especially surprising that those estimates that predated by far evidences of human crossing of the Strait of Gibraltar or fossil records were not envisaged under the light of these expected estimation biases and limitations (Guiller et al 2001;Libois et al 2001;Michaux et al 2003;Brandli et al 2005;Cosson et al 2005). Recent methods that calculate simultaneously times of divergence, population sizes and migration rates, were designed to circumvent this bias (e.g.…”
Section: Translocation Scenarios and Historical Demography Of The Eurmentioning
confidence: 99%
“…This is consistent with other European carnivores, especially mustelids, like wolverines (Walker et al, 2001), otters (Cassens et al, 2000;Morales, 2002), polecats, pine martens (Davison et al, 2001) and wolves (Vila et al, 1999). However, the low variation contrasts with the situation in other mammals, such as brown bears (Ursus arctos) (Taberlet et al, 1998), hedgehogs (Erinaceus europaeus) (Seddon et al, 2001), shrews (Sorex araneus, S. minutus and Crocidura suaveolens) (Taberlet et al, 1994(Taberlet et al, , 1998Bilton et al, 1998), and the rodents Apodemus sylvaticus (Michaux et al, 2003;Libois et al, 2001), Myopus schisticolor (Federov et al, 1996), Arvicola sp. (Taberlet et al, 1998), Microtus agrestis and Clethrionomys glareolus (Jaarola and Tegelstro¨m, 1995;Bilton et al, 1998).…”
Section: The Phylogeography Of European Minkmentioning
confidence: 88%
“…In most cases, a strong geographic structure of the genetic variability has been found throughout Europe, with different lineages arising from putative refugia in Iberia (Spain and Portugal), Italy, the Balkans and the Caucasus (Michaux et al, 1996(Michaux et al, , 1998(Michaux et al, , 2003Santucci et al, 1998;Taberlet et al, 1998 ;Libois et al, 2001;Hewitt, 1999). Yet some species, especially wideranging carnivores, exhibit little geographic structure between the proposed refugia.…”
Section: Introductionmentioning
confidence: 99%
“…In North Africa, paleontological data attest the presence of the wood mouse since 10,000 years only (Dobson, 1998;Dobson and Wright, 2000). Libois et al (2001) and Michaux et al (2003) showed that North African A. sylvaticus reached North Africa via the Strait of Gibraltar as a result of anthropogenic introductions during the Holocene. Heligmosomoides phylogeographic data in this region confirms this scenario as the Moroccan parasite population clusters within the south western European clade 2.…”
Section: Regional Co-differentiation Between Heligmosomoides and A Smentioning
confidence: 99%